Strength in numbers or guilt by association? Intragroup effects of female chief executive announcements - Dixon‐Fowler, Heather R.; Ellstrand, Alan E.; Johnson, Jonathan L. (Strategic Management Journal, 2013)
We predict that the media reports on female CEOs as a coherent group, whereas male CEOs are treated as individuals by the media. We also suggest that the resulting investors' perceptions of group entitativity of female‐led firms may not only influence the succession event–performance relationship at the focal firm, but may also have a significant effect on the value of other female‐led companies. Results of a text analysis and an event study of appointments of female CEOs to Fortune 1000 firms provide support for these predictions . Copyright © 2013 John Wiley & Sons, Ltd.